A novel water-soluble fluorescent polymer based on perylene bisimides dyes: one-pot preparation and its bio-imaging. Issue 6 (12th April 2016) - Tan, Haijian; Liu, Hongmei; Liu, Yaojun; Duan, Wenfeng; Yi, Xuegang; Wu, Yonggang; Zhao, Hongchi; Bai, Libin
Abstract: Perylene bisimides dye-based water-soluble fluorescent polymerP3, N, N '-bis(3-amyl)-1-bromo-7-{4'-[3''-( S -poly( N -acryloyl ethylene diamine hydrochloride)-2'''-methyl propionic acid)propionyloxy hexyloxy]phenyl} perylene-3, 4:9, 10-tetracarboxylic bisimides, was synthesized with polyelectrolyte modification via one-pot reaction (the reduction reaction of trithioester and click reaction between the thiol group and carbon–carbon double bond were simultaneously conducted in one pot with high conversion). One-pot method can overcome the limitation that usual click reaction between thiol and other groups has low conversion because thiol group is subject to rapid oxidation during purification and storage. Chemical, structural, and optical properties ofP3 and intermediate products were fully characterized by nuclear magnetic resonance spectroscopy, Fourier transform infrared, gel permeation chromatograph, UV–vis spectra, and fluorescence spectra, respectively. The results revealed thatP3 displayed excellent water solubility and not only exhibited red strong fluorescence emission band in water but also had the similar photoluminescent spectra to those of intermediate products (M4 andP2 ) in chloroform. Allowing for the potential application in biological detection field, cell viability and live cell imaging with the presence ofP3 were further investigated with Hela cells. The results showed thatP3 had low cytotoxicity with strong intracellular fluorescence entry. Meanwhile, with the augment of concentration ofP3 (0–0.500 mg mL −1 ), the cell uptake and accumulation ofP3 increased and thereby result in enhancement of the intracellular fluorescence. These experiment results suggested thatP3 had enormous potential as a fluorescence probe to be an important component in biological detection field.